Using comic books with pre-intermediate language students for reading comprehension and vocabulary recognition - León, Warner Alonso Salazar (2019)
The purpose of this study is to explore the effects of using comic books with a group of pre-intermediate languagestudents for reading comprehension and vocabulary recognition. For this research, 12 volunteer students from apublic university participated in a six-session itinerary. A pre-test and post-test applied to the 12 participants wherethey solved reading comprehension and vocabulary exercises using a comic book. In four more sessions, a groupof 6 participants worked on the exercises using a comic while the other 6 volunteers did the same using only thetranscription of the comic’s text. When the pilot study finished, those students were interviewed about their experienceduring the project and the effects on their performance. The results of the quantitative and qualitative dataanalysis showed that all the participants that used comics, regardless of proficiency and text level, performed betteron reading comprehension and vocabulary recognition than the ones using the transcripts. The findings of the studyconfirm that comics can be a motivation for reluctant readers and an effective tool for literacy and language learning.The results of the study are discussed along with the existing literature on the use of visuals for developing readingskills. Implications for language teachers and some suggestions for further research are also provided.